Diversity of intestinal microbiota and inflammatory cytokines after severe trauma - Chang-qing Liu; Jie Yang; Hong-fei Ren; Guang-neng Liao; Zhe Yin; Shi-lin Gao; Qiu-jing Du; Xing-zhu Yuan; Hanif Ullah; Ka Li (Scientific Reports)
Abstract Accumulating evidence has reported that the intestinal microbiota could play important roles in the occurrence and progression of severe trauma. However, the hypothesized potential targeted intestinal microbiota to mediate and regulate the levels of inflammatory cytokines and promote rapid recovery of body after severe trauma remains unclear. This study was aimed to explore the changes and correlation of intestinal microbiota and inflammatory cytokines in rats with severe crush and fracture trauma. The controlled laboratory study design was used, and a crush and fracture severe trauma rat model was established. 16S rRNA high-throughput gene sequencing and ELISA were used to analyze the changes in intestinal microbiota and inflammatory cytokines within one week after trauma. The correlation between intestinal microbiota and inflammatory cytokines was also analyzed. Loss of overall diversity and expansion of intestinal microbiota in the rats due to severe trauma was observed. Specifically, there was a significant increase in the abundance of Muribaculaceae [LDA (Linear Discriminant Analysis)-value = 4.814, P = 0.014] after severe trauma, while Prevotella (LDA-value = 5.235, P = 0.020) and Alloprevotella (LDA-value = 4.443, P = 0.015) were slightly lower in the trauma group than in the control group. The levels of inflammatory cytokines (IL-1α, IL-6, IL-8 and TNF-α) in the trauma group decreased from the first day to the third day and continued to increase until one week after the trauma. Prevotellaceae_UCG_001 was correlated with TNF-a (R = 0.411, P = 0.033); Lactobacillus was negatively correlated with IL-6 (R = − 0.434, P = 0.024) and IL-1α (R = − 0.419, P = 0.030) and positively correlated with IL-8 (R = 0.391, P = 0.045); and Lachnospiraceae_NK4A136_group (R = − 0.559, P = 0.027) and Muribaculaceae (R = − 0.568, P = 0.024) were negatively correlated with IL-8. Severe trauma shows stress-like activities by negatively modulating intestinal microbiota and affecting certain inflammatory cytokines contributing to host health, which implies that the regulation of potentially targeted intestinal microbiota, and further mediating and maintaining the homeostasis of inflammatory cytokines, is expected to promote the accelerating recovery of the body after severe trauma.